RELIGIOUS TOLERANCE IS A FACTOR OF DEMOCRATIC DEVELOPMENT (Neo Scientific Peer Reviewed Journal, 2024)
Religious tolerance, that is, showing respect and tolerance for different religious beliefs, is an important factor in the stable and democratic development of society. This situation is especially important for multi-ethnic and multi-religious countries. Religious tolerance not only guarantees religious freedom, but also serves to ensure social cooperation, peace and stability. This article talks about religious tolerance, its essence and its place in a democratic society.